2018
DOI: 10.1111/1755-6724.13686
|View full text |Cite
|
Sign up to set email alerts
|

Modes of Shale‐Gas Enrichment Controlled by Tectonic Evolution

Abstract: The typical characteristics of shale gas and the enrichment differences show that some shale gases are insufficiently explained by the existing continuous enrichment mode. These shale gases include the Wufeng–Longmaxi shale gas in the Jiaoshiba and Youyang Blocks, the Lewis shale gas in the San Juan Basin. Further analysis reveals three static subsystems (hydrocarbon source rock, gas reservoirs and seal formations) and four dynamic subsystems (tectonic evolution, sedimentary sequence, diagenetic evolution and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Some related studies have shown that a large amount of coalbed methane, which belongs to secondary biogas, is produced by microbial action when the source rocks are uplifted to a shallow depth (Wang et al 2018). Tectonic evolution is an important dynamic subsystem of shale gas enrichment system as the different strength has a distinct effect on the preservation of shale gas (Li and Ou 2018). In view of the complexity of the tectonic activities impact on shale gas enrichment and preservation, the prospective exploration potential of Well BC1 and TC1 still needs further detailed and comprehensive analysis.…”
Section: Implication For Shale Gas Exploration and Future Studiesmentioning
confidence: 99%
“…Some related studies have shown that a large amount of coalbed methane, which belongs to secondary biogas, is produced by microbial action when the source rocks are uplifted to a shallow depth (Wang et al 2018). Tectonic evolution is an important dynamic subsystem of shale gas enrichment system as the different strength has a distinct effect on the preservation of shale gas (Li and Ou 2018). In view of the complexity of the tectonic activities impact on shale gas enrichment and preservation, the prospective exploration potential of Well BC1 and TC1 still needs further detailed and comprehensive analysis.…”
Section: Implication For Shale Gas Exploration and Future Studiesmentioning
confidence: 99%
“…As a result, marginal uplifts were formed, such as the Central Sichuan Uplift, Central Guizhou Uplift, and the Xuefeng Uplift. This led to restricted shallow water areas surrounded by uplifts, and asedimentary environment characterized by low-energy, under-compensation, and anoxic conditions (Gao et al, 2014a;Mu et al, 2014;Ran et al, 2016;Zou et al, 2015Nie et al, 2017;Li et al, 2018). Then, affected by tectonic movements and two large-scale global transgressions, a set of thin siliceous shale layers was deposited during the Late Ordovician WF Fm, which contained abundant graptolites, such as Amplexograptus, Dicellograptus, Tangyagraptus, and Diceratograptus (Chen et al, 2000Wang et al, 2015;Nie et al, 2017).…”
Section: Geological Setting and Samplesmentioning
confidence: 99%
“…After the oil companies, such as PetroChina and Sinopec, explored the marine shale gas in this stratum, shale gas fields such as Weiyuan, Changning, Zhaotong, Fushun-Yongchuan, Dingshan, and Jiaoshiba have been built since 2010, and good industrial production capacity has been obtained [7][8][9][10]. Predecessors did researches on shale reservoir characteristics [11][12][13][14][15][16][17], shale gas accumulation mechanism [18][19][20][21][22], and shale gas preservation conditions [23][24][25][26][27][28] and have yielded a series of scientific research results. Organic matter is the material basis for hydrocarbon generation in shale and is also the main reservoir space and seepage channel for shale gas.…”
Section: Introductionmentioning
confidence: 99%